The effect of hypoxia-mimicking responses on improving the regeneration of artificial vascular grafts. (April 2021) - Rafique, Muhammad; Wei, Tingting; Sun, Qiqi; Midgley, Adam C.; Huang, Ziqi; Wang, Ting; Shafiq, Muhammad; Zhi, Dengke; Si, Jianghua; Yan, Hongyu; Kong, Deling; Wang, Kai
Abstract: Cellular transition to hypoxia following tissue injury, has been shown to improve angiogenesis and regeneration in multiple tissues. To take advantage of this, many hypoxia-mimicking scaffolds have been prepared, yet the oxygen access state of implanted artificial small-diameter vascular grafts (SDVGs) has not been investigated. Therefore, the oxygen access state of electrospun PCL grafts implanted into rat abdominal arteries was assessed. The regions proximal to the lumen and abluminal surfaces of the graft walls were normoxic and only the interior of the graft walls was hypoxic. In light of this differential oxygen access state of the implanted grafts and the critical role of vascular regeneration on SDVG implantation success, we investigated whether modification of SDVGs with HIF-1α stabilizer dimethyloxalylglycine (DMOG) could achieve hypoxia-mimicking responses resulting in improving vascular regeneration throughout the entirety of the graft wall. Therefore, DMOG-loaded PCL grafts were fabricated by electrospinning, to support the sustained release of DMOG over two weeks. In vitro experiments indicated that DMOG-loaded PCL mats had significant biological advantages, including: promotion of human umbilical vein endothelial cells (HUVECs) proliferation, migration and production of pro-angiogenic factors; and the stimulation of M2 macrophage polarization, which in-turn promoted macrophage regulation of HUVECs migration and smooth muscle cells (SMCs) contractile phenotype. These beneficial effects were downstream of HIF-1α stabilization in HUVECs and macrophages in normoxic conditions. Our results indicated that DMOG-loaded PCL grafts improved endothelialization, contractile SMCs regeneration, vascularization and modulated the inflammatory reaction of grafts in abdominal artery replacement models, thus promoting vascular regeneration.